The Effect Of Management Ownership, Leverage, Firm Size, And Profitability On Social Disclosure In Annual Reports Of Manufacturing Company (Empirical Study On Manufacturing Company Listed In Idx) (Proceeding Fakultas Ekonomi, 2012)
Products of accounting in the form of financial statement–annual report is the exposure of the report containing the accountability of the management of operational activities to the shareholders, but now need to extend this paradigm to be accountable to all stakeholders. This study is an empirical study conducted in manufacturing companies listed in IDX are intended to identify and examine the effect of management ownership, leverage, size, and profitability on social disclosure (Sustainable Reporting) in their annual reports during the period 2007-2010. The results of this study indicate that management ownership and leverage has no effect on the disclosure of social reporting in annual reports, whereas firm size and profitability have an influence on social disclosure in annual reports. Keywords: Social Disclosure, Sustainable Reporting, Management Ownership, Leverage, Firm Size, Profitability